PENGEMBANGAN MEDIA ARTICULLATE STORYLINE 3 BERBASIS SAINTIFIK PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS III SEKOLAH DASAR - Anggraini, Tri Suci Anggraini Suci; Reinita (Jurnal PGSD, 2022)
This research  is motivated by the use of learning media which only focuses on the use of text books in the delivery of learning materials, and the use of technology as a learning medium in learning activities is still rarely used. The purpose of the research was to develop a scientific based Articulate Storyline 3 media in integrated learning in the third grade of elementary school. The type of research used is research an development (R&D) research or development research. The model used in this study is the ADDIE model. The ADDIE model has five stages in its development, namely Analysis, Design, Development, Implementation, and Evaluation. The results of this study stated that the use of scientific based Articulate Storyline 3 learning media obtained a valid category with the results of material validation 83.95%, media validation 76.6% and language validation 82%. the result of the practicality test are stated to be very practical. This is obtained from the teacher response questionnaire and the student response questionnaire for class III SD Negeri 02 Jambak Lubuk Sikaping attitude where the results obtained are 88.6% student response questionnaires. Thus, the scientific based Articulate Storyline 3 learning media in integrated thematic learning in grade III elementary school is declared valid and very practical.